Conception of Mary According to Nicolaus Biceps OP in the Context of the Dominican Education System - Kochaniewicz, Bogusław; Łoza, Agnieszka; Zega, Włodzimierz (Verbum Vitae, 2024)
The aim of the article is to present the interpretation of the conception of the Blessed Virgin Mary contained in the commentary on the Sentences by Nicolaus Biceps in the context of the educational system of the Dominican Order. The specified research goal was achieved in the following way. First, the system of intellectual formation in the Dominican Order was analysed based on the resolutions of the general chapters, and then the relevant contained in the 14th-century work was presented. This allowed us to capture the position of the Czech Dominican, his method of argumentation, the sources on which he based his reflection, as well as the theological problems he had to face when commenting on the issue of the conception of the Blessed Virgin Mary at the University of Prague. Finally, this approach allowed us to find an answer to the question to what extent the Dominican educational system influenced the interpretation of the conception of Mary by medieval Dominican theologians and the consolidation of their negative position towards the Immaculate Conception of Mary.